THE RELATIONSHIP OF REGISTRATION WAITING TIME WITH PATIENT SATISFACTION AT THE OUTSTANDING PATIENT REGISTRATION PLACE - Jul Asdar putra samura; Balqis Wasliati; Raja Safriana Fadillah (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2022)
Patient waiting time in service at outpatient registration is one of the important factors that will determine the initial image of the hospital. Patient waiting time is also a potential component as a cause of dissatisfaction. Long waiting times at outpatient registration will reduce patient comfort. This study aims to determine the relationship between waiting time for registration with patient satisfaction at the outpatient registration area at Grandmed Lubuk Pakam Hospital. This type of research is analytic observational with cross sectional design. The population in this study were all Outpatients (TPPRJ). A sample of 62 people was drawn by purposive sampling technique. Methods of collecting data by direct interviews using a questionnaire, data analysis using the Chi-square test. Based on the results of the study, it is known that the waiting time for registration in the fast category is 62.9%. Patient satisfaction in the satisfied category was 59.7%. There is a relationship between waiting time for registration and patient satisfaction at the Outpatient Registration Center. p-value (= 0.022) < (= 0.05). It is recommended for Outpatient Registration Officers at Lubuk Pakam Hospital, must pay attention to the length of waiting time in Outpatient Registration, work faster and more precisely according to SOPs so that patients are always satisfied, happy with the services that have been provided by officers.